Negative electrode and lithium ion secondary battery comprising same

By uniformly distributing carbon materials and metals in the negative active material layer of all-solid lithium-ion secondary batteries, the problem of low surface roughness is solved, and the working characteristics and energy density of the battery are significantly improved.

CN119487637APending Publication Date: 2025-02-18LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380047806.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-31
Filing Date
2023-11-01
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the existing all-solid-state lithium-ion secondary batteries, it is difficult to form a thin film with low surface roughness in the negative electrode active material layer, which affects the working characteristics of the battery.

Method used

By uniformly distributing the carbon material and metal in the negative electrode active material layer, the surface roughness is significantly improved, and an excellent carbon material-metal composite is formed.

Benefits of technology

The working characteristics of lithium-ion secondary batteries are improved, and the energy density and output performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487637A_ABST
    Figure CN119487637A_ABST
Patent Text Reader

Abstract

The present invention provides a negative electrode and a lithium ion secondary battery including the same, the negative electrode including a current collector and negative electrode active material layers, in which the negative electrode active material layers include one or more layers, and any of the negative electrode active material layers included in the negative electrode active material layers contains oxygen in an amount of 2 to 10 at%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0144769 filed on November 2, 2022 and Korean Patent Application No. 10-2023-0148135 filed on October 31, 2023, the entire contents of which are incorporated herein by reference.

[0002] The invention relates to a negative electrode and a lithium ion secondary battery comprising the negative electrode. Background Art

[0003] Recently, all-solid-state secondary batteries using solid electrolytes as electrolytes have attracted much attention. In order to increase the energy density of such all-solid-state secondary batteries, it has been proposed to use lithium as a negative electrode active material. The capacity density (capacity per unit weight) of lithium is about 10 times that of graphite, which is commonly used as a negative electrode active material. Therefore, if lithium is used as a negative electrode active material, the output can be increased while making the all-solid-state secondary battery thinner.

[0004] As an all-solid-state lithium ion secondary battery, for example, an anode-less lithium ion secondary battery including a negative electrode active material layer containing a metal that forms an alloy with lithium and a carbon material is known.

[0005] The anode-free lithium ion secondary battery as described above is driven by a mechanism in which metallic lithium is precipitated in the negative electrode active material layer or between the negative electrode active material layer and the current collector during charge, and the corresponding metallic lithium is ionized and moves toward the positive electrode during discharge.

[0006] The negative electrode active material layer is formed into a very thin film having a micro thickness, but there is a problem that it is difficult to form the negative electrode active material layer with a low surface roughness.

[0007] [Prior art literature]

[0008] [Patent Document]

[0009] Korean Patent Publication No.10-2015-0064697 Summary of the invention

[0010] [Technical issues]

[0011] The present invention is designed to solve the above-mentioned problems of the prior art, and an object of the present invention is to provide a negative electrode and a lithium ion secondary battery with improved performance comprising the negative electrode, which greatly improves the operating characteristics of the battery by uniformly distributing carbon materials and metals in the negative electrode active material layer and significantly improving the surface roughness.

[0012] [Technical solution]

[0013] In order to achieve the above object, the present invention provides a negative electrode, which comprises:

[0014] current collector and negative electrode active material layer,

[0015] The negative electrode active material layer includes more than one layer, and any one of the negative electrode active material layers contains oxygen in an amount of 2 to 10 atomic %.

[0016] In addition, the present invention provides a lithium ion secondary battery, which includes the above-mentioned negative electrode, a positive electrode, and an electrolyte between the negative electrode and the positive electrode.

[0017] [Beneficial Effects]

[0018] The negative electrode of the present invention provides an effect of greatly improving the operating characteristics of a battery by including a negative electrode active material layer in which a carbon material and a metal are uniformly distributed and the surface roughness is significantly improved.

[0019] In addition, the lithium ion secondary battery of the present invention provides excellent operating characteristics by including the negative electrode active material layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 and 2 It is a cross-sectional view schematically showing the structure of the lithium ion secondary battery of the present invention.

[0021] Figure 3 This is a graph showing the particle size distribution of the carbon material-metal composite of the present invention.

[0022] Figure 4 This is a graph showing the analysis results of the rheological properties of a slurry containing a negative electrode active material of the carbon material-metal composite of the present invention.

[0023] Figure 5 and 6 It is a graph showing the cycle characteristics of a lithium ion secondary battery including a negative electrode active material layer containing the carbon material-metal composite of the present invention.

[0024] Figure 7 1s spectra of carbon (C) contained in the negative electrode active material layers prepared in Example 2, Comparative Example 3, and Comparative Example 4 are shown.

[0025] Figure 8 The peak deconvolution results in the O1s spectra of oxygen contained in the negative electrode active material layers prepared in Example 2, Comparative Example 3, and Comparative Example 4 are shown.

[0026] Fig. 9 SEM images of surfaces of negative electrode active material layers stacked on the negative electrodes prepared in Example 2 of the present invention and Comparative Example 5 are shown.

[0027] Fig.10 Laser confocal microscope photographs showing the measurement results of the surface roughness of the negative electrode active material layers stacked on the negative electrodes prepared in Example 2 of the present invention and Comparative Example 5 are shown. DETAILED DESCRIPTION

[0028] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.

[0029] The terms and words used in this specification and claims should not be interpreted as limited to general or dictionary terms, but should be interpreted based on the principle that the inventor can appropriately define the concept of the term to describe his invention in the best possible way with the meaning and concept consistent with the technical idea of ​​the present invention. In addition, the terms used herein are only used to describe exemplary embodiments and are not intended to limit the present invention. Singular expressions include plural expressions unless the context clearly dictates otherwise.

[0030] When it is mentioned that a certain component is "connected, provided or arranged" to another component, it should be understood that it can be directly connected or arranged to another component, but other components may also exist therebetween. On the other hand, when it is mentioned that a certain component is "directly connected or arranged" to another component, it should be understood that no other components exist therebetween. At the same time, other expressions describing the relationship between components, such as "on top" and "directly on top" or "between" and "immediately between" or "adjacent to" and "directly adjacent to", etc., should also be interpreted similarly.

[0031] As used herein, the term "combination" is inclusive of mixtures, alloys, reaction products, and the like, unless specifically stated otherwise.

[0032] The negative electrode of the present invention comprises a current collector and a negative electrode active material layer.

[0033] The negative electrode active material layer includes more than one layer, and any one of the layers contains oxygen in an amount of 2 to 10 atomic %.

[0034] The lower limit of the oxygen content may be 2.5 atomic % or more, 3 atomic % or more, 3.5 atomic % or more, 4 atomic % or more, 4.5 atomic % or more, or 5 atomic % or more. In addition, the upper limit of the oxygen content may be 9.5 atomic % or less, 9 atomic % or less, 8.5 atomic % or less, 8 atomic % or less, 7.5 atomic % or less, 7 atomic % or less, 6.5 atomic % or less, 6 atomic % or less, 5.5 atomic % or less, 5 atomic % or less, 4.5 atomic % or less, 4 atomic % or less, 3.5 atomic % or less, or 3 atomic % or less. The oxygen content may be a range consisting of a combination of a lower limit and an upper limit. Specifically, the oxygen content may preferably be 2.5 to 10 atomic %.

[0035] In the above, if the oxygen content is less than 2 atomic %, the surface roughness of the negative electrode active material layer is significantly reduced, so it is not preferred, and if the oxygen exceeds 10 atomic %, the performance of the battery is deteriorated due to the side reaction with the solid electrolyte, so it is not preferred.

[0036] In one embodiment of the present invention, any negative electrode active material layer may further contain 65 to 85 atomic % of carbon and 0.5 to 5 atomic % of metal elements, more preferably 74 to 85 atomic % of carbon and 0.5 to 3 atomic % of metal elements.

[0037] In one embodiment of the present invention, any negative electrode active material layer may further contain 5 to 25 atomic % of fluorine (F), more preferably 10 to 20 atomic % of fluorine (F).

[0038] In one embodiment of the present invention, any negative electrode active material layer may further contain 0.01 to 1 atomic % of sulfur (S), more preferably 0.01 to 0.5 atomic % of sulfur (S).

[0039] In one embodiment of the present invention, any one of the negative active material layers may contain 2 to 10 atomic % of oxygen, 65 to 85 atomic % of carbon, 0.5 to 5 atomic % of metal elements, and 5 to 25 atomic % of fluorine (F).

[0040] In addition, any one of the negative electrode active material layers may more preferably contain 2.5 to 5 atomic % of oxygen, 74 to 85 atomic % of carbon, 0.5 to 3 atomic % of a metal element, and 10 to 20 atomic % of fluorine (F).

[0041] In addition, any negative electrode active material layer may further contain sulfur (S) in addition to the above components.

[0042] In the above, the composition ratio of any negative electrode active material layer can be measured using a photoelectron spectroscopy (XPS or ESCA). For example, the composition ratio of any negative electrode active material layer can be measured using a Nexsa4 (Thermo Fisher Scientific) device.

[0043] In one embodiment of the present invention, any negative electrode active material layer may include carbon material particles and metal particles, and the carbon material particles may be, for example, amorphous carbon material particles. However, the carbon material particles are not limited to amorphous particles. Specific examples of amorphous carbon materials may be carbon black such as acetylene black, furnace black and Ketjen black, graphene or a combination thereof.

[0044] If the amorphous carbon material particles contain pores, the size of the pores may be 1 nm or less, preferably 0.5 nm or less. However, it may be more preferred that the amorphous carbon material particles do not contain pores. This is because, if the amorphous carbon material particles contain pores, lithium may precipitate inside the pores, such lithium may be deactivated, and the amount of lithium thus deactivated may increase with repeated charging and discharging.

[0045] The pore size in the amorphous carbon material particles can be measured, for example, by nitrogen adsorption experiments or by transmission electron microscopy.

[0046] The carbon material particles may be carbon material particles containing 3 to 10 atomic % of oxygen. In the above, if the content of oxygen is less than 3 atomic %, the surface roughness of the negative electrode active material layer is significantly reduced, so it is not preferred. If the oxygen exceeds 10 atomic %, the performance of the battery is deteriorated due to the side reaction with the solid electrolyte, so it is not preferred.

[0047] In the above, the lower limit of the oxygen content may be 3.5 atomic % or more, 4 atomic % or more, or 4.5 atomic % or more. In addition, the upper limit of the oxygen content may be 9.5 atomic % or less, 9 atomic % or less, 8 atomic % or less, 7.5 atomic % or less, 7 atomic % or less, 6.5 atomic % or less, 6 atomic % or less, or 5.5 atomic % or less. The oxygen content may be a range consisting of a combination of a lower limit and an upper limit. Specifically, the oxygen content may preferably be 5 to 10 atomic %.

[0048] In one embodiment of the present invention, oxygen may be present in the form of being contained in a functional group bound to the carbon material particles. In addition, the functional group may include one or more selected from the group consisting of a carboxyl group, a hydroxyl group, an ether group, an ester group, an aldehyde group, a carbonyl group, and an amide group.

[0049] Carbon material particles having an oxygen content of 3 to 10 atomic % can be produced by, for example, a method of oxidizing a carbon material. Specifically, oxygen functional groups can be introduced into the surface of the carbon material by treating the carbon material with an acid and reacting it at a temperature of 25° C. to 60° C. while stirring. The type of acid is not particularly limited, and any acid capable of introducing oxygen functional groups into the surface of the carbon material can be used. The acid can include, for example, sulfuric acid, nitric acid, or a mixture thereof, and an oxidizing agent such as potassium permanganate can be used.

[0050] The oxygen content contained in the carbon material can be measured using a photoelectron spectrometer (XPS or ESCA). For example, the oxygen content contained in the carbon material can be measured using a K-Alpha (Thermo Fisher Scientific) device.

[0051] In one embodiment of the present invention, oxygen may exist on the surface of the carbon material particles. The surface refers not only to the outer surface of the carbon material particles but also includes the surface of pores when pores exist.

[0052] In one embodiment of the present invention, the metal particles may be particles that form an alloy with lithium, and the metal particles may be particles of one or more selected from silver (Ag), gold, platinum, palladium, silicon, aluminum, bismuth, tin, indium and zinc.

[0053] In one embodiment of the present invention, it may be preferred that the metal particles contain silver (Ag).

[0054] In one embodiment of the present invention, any negative electrode active material layer may have the following surface roughness characteristics:

[0055] 0.01μm≤Sa≤0.3μm

[0056] 0.5μm≤Sz≤5μm

[0057] 500mm -1 ≤Spc≤1500mm -1

[0058] 0.005≤Sdr≤0.15.

[0059] If the surface roughness satisfies the above range, the overall characteristics of the battery can be improved, and in particular, the life characteristics can be improved. Specifically, if the surface roughness of the negative electrode active material layer exceeds the above range, the contact with the electrolyte layer in the direction toward the electrolyte is insufficient and is not conducive to the uniform precipitation of lithium in the direction toward the negative electrode current collector, so the characteristics of the battery may be deteriorated.

[0060] In the above, the surface roughness of the negative electrode active material layer can be measured using a microscope device. For example, the surface roughness can be measured using a 3D laser confocal microscope (manufactured by KEYENCE Corporation) device.

[0061] In the above, Sa (arithmetic mean height of the profile) can be at most 0.3 μm or less, 0.2 μm or less, 0.1 μm or less, 0.08 μm or less, or 0.075 μm or less, and at least 0.01 μm or more, 0.02 μm or more, 0.03 μm or more, 0.04 μm or more, 0.05 μm or more, 0.06 μm or more, or 0.07 μm or more. In addition, Sa can more preferably be in the range of 0.01 μm ≤ Sa ≤ 0.1 μm, but is not limited to these ranges, and can be set to a range of a combination of a maximum value and a minimum value. Sa represents the average value of the absolute value of the height difference between each point relative to the average surface of the surface.

[0062] In the above, Sz (maximum height roughness of the profile) may be at most 5 μm or less, 4 μm or less, 3 μm or less, 2 μm or less, or 1.5 μm or less, and at least 0.5 μm or more, 0.8 μm or more, 1 μm or more, 1.1 μm or more, 1.2 μm or more, or 1.3 μm or more. In addition, Sz may more preferably be in the range of 0.5 μm ≤ Sz ≤ 1.6 μm, but is not limited to these ranges, and may be set to a range of a combination of a maximum value and a minimum value. Sz represents the maximum height roughness in a single plane, that is, the distance between the highest point and the lowest point in a single plane.

[0063] In the above, Spc (roughness expressed in peaks) can be up to 1500 mm -1 Below, 1400mm -1 Below, 1300mm -1 Below, 1200mm -1 Below, 1100mm -1 Below, or 1000mm -1 Below, and at least 500mm -1 Above, 600mm -1 Above, 700mm -1 Above, 800mm -1 Above, or 900mm -1 In addition, Spc can be more preferably 500mm -1 ≤Spc≤1100mm -1 The range of is within, but not limited to, these ranges, and can be set to a range of a combination of a maximum value and a minimum value. Spc is a measure of roughness expressed in terms of the number of peaks, that is, a measure of peak steepness.

[0064] In the above, Sdr (degree of increase in interface area) can be at most 0.15 or less, 0.1 or less, 0.05 or less, 0.03 or less, or 0.02 or less, and at least 0.005 or more, 0.01 or more, or 0.015 or more. In addition, Sdr can more preferably be in the range of 0.005≤Sdr≤0.03, but is not limited to these ranges, and can be set to a range of a combination of a maximum value and a minimum value. Sdr refers to the degree of increase in interface area, that is, the area ratio increased relative to the area of ​​the measurement area when the expansion area (surface area of ​​the measurement shape) is observed vertically.

[0065] In the above, the meanings of Sa, Sz, Spc, and Sdr are described, but they are the same as those commonly used in the art.

[0066] In one embodiment of the present invention, the porosity of any negative electrode active material layer may be 55% to 70%, more preferably 62% to 67%. If the porosity satisfies the above range, a desired effect can be obtained in ensuring uniformity of the coating in the electrode.

[0067] In the above, the porosity of the negative electrode active material layer is a value calculated using the weight and thickness values ​​of the negative electrode active material layer.

[0068] In one embodiment of the present invention, any negative electrode active material layer may include 60 to 80 weight % of carbon material particles containing 3 to 10 atomic % of oxygen, 10 to 30 weight % of metal particles and 3 to 20 weight % of binder. In addition, any negative electrode active material layer may include 65 to 75 weight % of carbon material particles containing 3 to 10 atomic % of oxygen, 20 to 30 weight % of metal particles and 4 to 8 weight % of binder.

[0069] In one embodiment of the present invention, the carbon material particles and the metal particles may be included in the form of a carbon material-metal composite.

[0070] Recently, as an all-solid lithium ion secondary battery, for example, various studies have been conducted on an anode-free lithium ion secondary battery including a negative electrode active material layer containing a metal that forms an alloy with lithium and a carbon material.

[0071] The negative electrode active material layer is formed into a very thin film with a micro thickness and is manufactured in the form of a carbon material-metal composite containing carbon material particles and metal particles combined. However, conventional carbon material-metal composites have a problem that carbon material particles and metal particles are difficult to be uniformly distributed.

[0072] In addition, conventional carbon material-metal composites have a problem that it is very difficult to form a composite with a small particle size. That is, if the particle size of the carbon material-metal composite is too large compared to a thin film with a micro thickness, it is difficult to form a negative electrode active material layer with excellent surface roughness and thus the operating characteristics of the battery are also reduced, so it is very important to prepare a carbon material-metal composite with a small particle size.

[0073] The present invention provides the effect of significantly improving the above-mentioned problems of the prior art.

[0074] That is, the carbon material-metal composite forms a carbon material-metal composite having a significantly smaller particle size than when prepared using a conventional carbon material. The carbon material forming the composite contains 3 atomic % or more of oxygen, and thus is fully mixed with the metal particles and has the property of being uniformly distributed with the metal particles. Therefore, a carbon material-metal composite having excellent component uniformity can be prepared. In addition, due to the above reasons, a carbon material-metal composite having a small and uniform particle size can be prepared.

[0075] In one embodiment of the present invention, the carbon material-metal composite may be composed of one or more bonds selected from the group consisting of chemical bonds between carbon material particles and metal particles, van der Waals bonds between carbon material particles and metal particles, and bonds between carbon material particles and metal particles via a binder. The chemical bond may be a metal (e.g., Ag)-O bond between a metal particle (e.g., Ag) and oxygen contained in the carbon material.

[0076] In one embodiment of the present invention, the carbon material-metal composite may contain 60 to 90 wt% of the carbon material and 10 to 40 wt% of the metal based on the total weight. In addition, the carbon material-metal composite may contain 70 to 80 wt% of the carbon material and 20 to 30 wt% of the metal based on the total weight.

[0077] In addition, the carbon material-metal composite may further contain 3 to 10 wt % of a binder based on the total weight of the composite. For example, in the wet preparation of the carbon material-metal composite, a binder dissolved in a solvent together with carbon material particles and metal particles may be used. In this case, the binder may be contained in the carbon material-metal composite. If the binder is contained, the content of the above-mentioned carbon material may be contained in the range of the content reduced by the inclusion of the binder.

[0078] In one embodiment of the present invention, carbon material particles having a particle size (D50) of 10nm to 100nm or 20nm to 60nm may be used, and metal particles having a particle size (D50) of 20nm to 100nm, 20nm to 60nm, or 30nm to 60nm may be used.

[0079] In one embodiment of the present invention, the particle size (D50) of the carbon material-metal composite may be 0.1 μm to 0.5 μm. The upper limit of the particle size may be 0.4 μm or 0.3 μm.

[0080] In addition, the maximum particle size of the carbon material-metal composite may be 3 μm or less, 2 μm or less, 1.5 μm or less, or 1 μm or less.

[0081] If the particle size of the carbon material-metal composite is too large compared to a thin film with a micro thickness, it is difficult to form a negative electrode active material layer with excellent surface roughness and thus the operating characteristics of the battery are also reduced, so it is very important to prepare a carbon material-metal composite with a small particle size.

[0082] The reason why the operating characteristics of the battery deteriorate is that if the surface roughness of the negative electrode active material layer is large, the contact with the electrolyte layer in the direction toward the electrolyte is insufficient and it is not conducive to the uniform precipitation of lithium in the direction toward the negative electrode current collector.

[0083] In an anode-free lithium ion secondary battery, the thickness of the negative electrode active material layer may generally be formed in the range of 1 μm to 100 μm or 10 μm to 60 μm, specifically 10 μm, 20 μm, 30 μm, 40 μm or 50 μm, etc.

[0084] For example, if a carbon material-metal composite having a particle size of 10 μm is used to form a negative electrode active material layer having a thickness of 20 μm, it is apparently difficult to form a desired surface roughness.

[0085] If the maximum particle size of the carbon material-metal composite is 3 μm or less, the effect of improving the surface roughness can be more reliably obtained, which is preferred. On the other hand, when the maximum particle size exceeds 3 μm, it may be difficult to obtain excellent surface roughness when forming a thin film.

[0086] The particle size of the carbon material-metal composite can be measured using a particle size analyzer. For example, the particle size can be measured using a Mastersizer 3000 (Malvern panalytical) instrument.

[0087] The present invention relates to a slurry of negative electrode active material containing a carbon material-metal composite.

[0088] The slurry of negative electrode active material is 2.5s -1 The viscosity at a shear rate of 8 Pa·s or less, 7 Pa·s or less, 6 Pa·s or less, or 5 Pa·s or less.

[0089] The slurry of the negative electrode active material may contain 15 to 50 wt % of a carbon material-metal composite, 1 to 10 wt % of a binder (based on solid components) and 40 to 80 wt % of a solvent, preferably 25 to 35 wt % of a carbon material-metal composite, 1 to 5 wt % of a binder and 60 to 70 wt % of a solvent. In addition, the slurry may further contain additives contained in the slurry of the negative electrode active material in the art.

[0090] The present invention relates to a negative electrode active material layer comprising a carbon material-metal composite.

[0091] In the negative electrode active material layer, the carbon material and the metal are uniformly distributed and the surface roughness is excellent, thus providing an effect of improving the operating characteristics of a lithium ion secondary battery including the negative electrode active material layer.

[0092] In addition, the present invention provides a lithium ion secondary battery, comprising:

[0093] The negative electrode; the positive electrode; and an electrolyte between the negative electrode and the positive electrode.

[0094] The lithium ion secondary battery may be an anode-less battery.

[0095] A lithium ion secondary battery provides improved operating characteristics by including the negative electrode active material layer of the present invention.

[0096] In one embodiment of the present invention, the solid electrolyte may be a sulfide-based solid electrolyte.

[0097] In one embodiment of the present invention, the lithium ion secondary battery may be an anode-less battery.

[0098] Hereinafter, embodiments of the present invention will be described in more detail.

[0099] <Composition of all-solid-state lithium-ion secondary battery>

[0100] Figure 1 A cross-sectional view schematically showing a schematic configuration of an all-solid-state lithium-ion secondary battery according to an embodiment of the present invention is shown.

[0101] The all-solid-state lithium-ion secondary battery 100 according to the embodiment of the present invention is a so-called lithium-ion secondary battery that is charged and discharged by moving lithium ions between the positive electrode 10 and the negative electrode 20. Specifically, the all-solid-state lithium-ion secondary battery 100 is composed of a positive electrode 10, a negative electrode 20, and a solid electrolyte layer 30 provided between the positive electrode 10 and the negative electrode 20. Figure 1 shown.

[0102] (1) Positive electrode

[0103] like Figure 1 As shown, the positive electrode 10 includes a positive electrode current collector 12 and a positive electrode active material layer 14 which are sequentially disposed toward the negative electrode 20 .

[0104] The positive electrode current collector 12 may be in the form of a plate or foil. The positive electrode current collector 12 may be, for example, a metal selected from indium, copper, magnesium, stainless steel, titanium, iron, cobalt, nickel, zinc, aluminum, germanium and lithium, or an alloy of two or more of these metals.

[0105] The positive electrode active material layer 14 may reversibly intercalate and deintercalate lithium ions. The positive electrode active material layer 14 may include a positive electrode active material and a solid electrolyte.

[0106] The positive electrode active material may be a compound capable of intercalating / deintercalating lithium. Examples of the compound capable of intercalating / deintercalating lithium may be a compound represented by any one of the following formulae: Li a A 1-b B' b D'2 (where 0.90≤a≤1.8 and 0≤b≤0.5); Li a E 1-b B' b O 2-c D'c (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); LiE 2-b B' b O 4-c D' c (where 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b B' c D' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Co b B' c O 2-α F' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni 1-b-c Mn b B' c D' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α≤2); Li a Ni 1-b-c Mn b B' c O 2-α F' α (where 0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0<α<2); Li a Ni b E c G d O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1); Li a Ni b Co c Mn d G e O2 (where 0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0.001≤e≤0.1); Li a NeG b O2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li a MnG bO2 (where 0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn b O4 (where 0.90≤a≤1.8, 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiI'O2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2); and LiFePO4.

[0107] In the above formula, A is Ni, Co, Mn or a combination thereof; B' is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D' is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; F' is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; I' is Cr, V, Fe, Sc, Y or a combination thereof; J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.

[0108] Specific examples of the positive electrode active material may be lithium salts such as lithium cobalt oxide (hereinafter referred to as LCO), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide (hereinafter referred to as NCA), and lithium nickel cobalt manganese oxide (hereinafter referred to as NCM), lithium manganese oxide, and lithium iron phosphate, as well as lithium sulfide. The positive electrode active material layer 14 may contain only one selected from these compounds, or may contain two or more as the positive electrode active material.

[0109] The positive electrode active material may include a lithium salt of a transition metal oxide having a layered rock salt structure among the above-mentioned lithium salts. Here, the "layered rock salt structure" is a structure in which oxygen atomic layers and metal atomic layers are alternately and regularly arranged in the direction of the cubic rock salt structure, resulting in each atomic layer forming a two-dimensional plane. In addition, the "cubic rock salt structure" refers to a sodium chloride structure as one of the crystal structures. For example, the "cubic rock salt structure" refers to a structure in which the face-centered cubic lattices formed by positive ions and negative ions are offset from each other by 1 / 2 edges of the unit lattice.

[0110] The lithium salt of the transition metal oxide having such a layered rock salt structure may be, for example, a ternary lithium transition metal oxide such as LiNi x Co y Al z O2(NCA) or LiNi x Co y Mn zO2(NCM) (where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1). The positive electrode active material layer 14 can improve the energy density and thermal stability of the all-solid-state lithium-ion secondary battery 100 by including a lithium salt containing a ternary transition metal oxide having such a layered rock salt structure as the positive electrode active material.

[0111] Here, the shape of the positive electrode active material can be, for example, a particulate shape, such as a true spherical shape or an elliptical spherical shape. In addition, the particle size of the positive electrode active material is not particularly limited and can be within the range applicable to the positive electrode active material of a typical all-solid-state lithium-ion secondary battery. In addition, the content of the positive electrode active material in the positive electrode active material layer 14 is also not particularly limited as long as it is within the range applicable to the positive electrode of a typical all-solid-state lithium-ion secondary battery.

[0112] Of course, a material having a coating on the surface of the compound can be used, or a mixture of the compound and a compound having a coating can also be used. The coating can include a coating element compound such as an oxide or hydroxide of the coating element, a hydroxyoxide of the coating element, an oxycarbonate of the coating element, or a hydroxycarbonate of the coating element. The compounds constituting these coatings can be amorphous or crystalline. The coating elements contained in the coating can be Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The coating formation process can use any coating method (e.g., spraying, dipping, etc.) as long as it can coat in a manner that does not adversely affect the performance of the positive electrode active material by using these elements in the compound, and since those skilled in the art can well understand it, its detailed description will be omitted.

[0113] A specific example of the coating can be Li2O-ZrO2.

[0114] The solid electrolyte contained in the positive electrode active material layer 14 can be the same as or different from the solid electrolyte contained in the solid electrolyte layer 30 described later.

[0115] In addition, the positive electrode active material layer 14 can be a layer obtained by appropriately mixing additives such as a conductive agent, a binder, a filler, a dispersant, or an ion conductive aid, and the above positive electrode active material and solid electrolyte.

[0116] The conductive agent can be, for example, graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or metal powder. In addition, the binder can be, for example, styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, or polyethylene. In addition, the filler, the dispersant, the ion conductive aid, etc. can be known materials commonly used for the electrodes of all-solid-state lithium-ion secondary batteries.

[0117] (2) Negative electrode

[0118] The negative electrode 20 may include a negative electrode current collector 22 and a negative electrode active material layer 24 sequentially disposed toward the positive electrode 10 .

[0119] The negative electrode current collector 22 may be in the form of a plate or foil. The negative electrode current collector 22 may include a material that does not react with lithium, i.e., does not form any of an alloy or a compound with lithium. The material constituting the negative electrode current collector 22 may be, for example, copper, stainless steel, titanium, iron, cobalt, and nickel. The negative electrode current collector 22 may be composed of one of these metals, or may be composed of an alloy or a coating (coating) material of two or more of these metals.

[0120] The negative electrode active material layer 24 may not contain lithium in the negative electrode current collector 22, in the negative electrode active material layer 24, or between the negative electrode active material layer 24 and the solid electrolyte layer 30 in the initial state or in the state after being fully discharged. As described later, if the all-solid-state lithium ion secondary battery 100 according to the embodiment is overcharged, the negative electrode active material contained in the negative electrode active material layer 24 and the lithium ions moved from the positive electrode 10 form an alloy or a compound, and a metal layer 26 containing lithium as a main component may be formed (precipitated) on the negative electrode 20, such as Figure 2 The metal layer 26 may be precipitated and disposed between the negative electrode current collector 22 and the negative electrode active material layer 24 and / or in the negative electrode active material layer 24. The metal layer 26 containing lithium as a main component between the negative electrode current collector 22 and the negative electrode active material layer 24 may be disposed closer to the negative electrode current collector 22 than the negative electrode active material layer 24.

[0121] The negative electrode active material layer 24 according to the embodiment may include Ag as the negative electrode active material. Therefore, the metal layer 26 formed during overcharge may include a Li(Ag) alloy including a γ1 phase, a βLi phase, or a combination thereof in which Ag is solid-dissolved in lithium. Therefore, during discharge, only Li is dissolved in the Li(Ag) alloy constituting the metal layer 26, and solid-dissolved Ag remains, thereby suppressing the generation of voids. In this case, the content of Ag in the precipitated Li-Ag solid solution may be 60 wt % or less. If the content is within this range, the reduction in the average discharge potential due to the influence of Ag can be effectively suppressed. On the other hand, if the content of Ag in the precipitated Li-Ag solid solution is too small, the amount of Ag remaining during discharge is reduced, and the generation of voids may not be fully suppressed. To this end, the content of Ag in the precipitated Li-Ag solid solution may be 20 wt % or more, for example, 40 wt % or more.

[0122] If the content of Ag contained in the negative electrode active material layer 24 is too small, the amount of Ag remaining during discharge also decreases, so the generation of voids may not be suppressed. For this reason, in an initial state where charging and discharging are not performed, the content of Ag in the negative electrode active material layer 24 is 10 wt % or more, for example, 20 wt % or more, based on 100 wt % of the total weight of the negative electrode active material contained in the negative electrode active material layer.

[0123] The negative electrode active material layer 24 may further contain, for example, one or more selected from amorphous carbon, Au, Pt, Pd, Si, Al, Bi, Sn, In, and Zn as an optional negative electrode active material other than Ag.

[0124] The carbon material contained in the negative electrode active material layer 24 may preferably be amorphous carbon. However, the carbon material is not limited to amorphous carbon. Specific examples of amorphous carbon may be carbon black such as acetylene black, furnace black, and Ketjen black, graphene, or a combination thereof.

[0125] The sum of the negative electrode active materials other than Ag may be 50 wt % or more, for example 70 wt % or more, based on 100 wt % of the total weight of the negative electrode active materials contained in the negative electrode active material layer 24. The content of the negative electrode active materials other than Ag may be measured in the same manner as the Ag content.

[0126] The negative electrode active material layer 24 may further include a binder (binder). The negative electrode active material layer 24 may be stabilized on the negative electrode current collector 22 by including a binder (binder). The material constituting the binder (binder) may be, for example, a resin material such as styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, and polyethylene. The binder (binder) may be composed of one or more selected from these resin materials.

[0127] In addition, the negative electrode active material layer 24 may be in a state where additives used in conventional all-solid lithium ion secondary batteries (eg, fillers, dispersants, ion conductive agents, etc.) are appropriately blended. Specific examples of the additives are the same as those described in the positive electrode above.

[0128] The total thickness of the negative electrode active material layer 24 is not particularly limited, but may be 1 μm to 100 μm, or 10 μm to 60 μm. If the thickness of the negative electrode active material layer 24 is less than 1 μm, the performance of the all-solid-state secondary battery may not be sufficiently improved. If the thickness of the negative electrode active material layer 24 exceeds 100 μm, the resistance of the negative electrode active material layer 24 is high, and thus the performance of the all-solid-state secondary battery may not be sufficiently improved. If the above-mentioned binder is used, the thickness of the negative electrode active material layer 24 can be easily ensured at an appropriate level.

[0129] On the other hand, a film containing a material capable of forming an alloy or a compound with lithium is further included on the negative electrode collector 22 , and the film may be provided between the negative electrode collector 22 and the negative electrode active material layer.

[0130] The negative electrode current collector 22 does not react with lithium metal, but it may be difficult to deposit a smooth lithium metal layer thereon. The film may also serve as a wetting layer to allow lithium metal to be deposited evenly on the negative electrode current collector 22 .

[0131] The material used in the film that can form an alloy with lithium metal may include silicon, magnesium, aluminum, lead, silver, tin or a combination thereof. The material used in the film that can form a compound with lithium metal may include carbon, titanium sulfide, iron sulfide or a combination thereof. Within the limit of not affecting the electrochemical properties of the electrode and / or the redox potential of the electrode, the content of the material used in the film may be small. The film can be applied flatly on the negative electrode current collector 22 to prevent cracks from occurring during the charging cycle of the all-solid-state lithium-ion secondary battery 100. The film can be applied by methods such as physical vapor deposition (e.g., evaporation or sputtering), chemical vapor deposition or plating methods.

[0132] The thickness of the film may be 1 nm to 500 nm. The thickness of the film may be, for example, 2 nm to 400 nm. The thickness of the film may be, for example, 3 nm to 300 nm. The thickness of the film may be, for example, 4 nm to 200 nm. The thickness of the film may be, for example, 5 nm to 100 nm.

[0133] (3) Solid electrolyte layer

[0134] The solid electrolyte layer 30 is disposed between the positive electrode 10 and the negative electrode 20 (eg, between the positive electrode active material layer 14 and the negative electrode active material layer 24). The solid electrolyte layer 30 includes a solid electrolyte capable of transporting ions. The solid electrolyte layer 30 may include a sulfide-based solid electrolyte.

[0135] Sulfide-based solid electrolytes may include Li2S-P2S5, Li2S-P2S5-LiX (X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (m and n are positive numbers, Z is one of Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q(p and q are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, or In) or a combination thereof. The solid electrolyte may be composed of one material or two or more materials selected from these sulfide-based solid electrolyte materials.

[0136] The sulfide-based solid electrolyte may include a solid electrolyte represented by the following Formula 1:

[0137] <Formula 1>

[0138] Li x M' y PS z A w

[0139] in,

[0140] x, y, z and w are each independently 0 or more and 6 or less;

[0141] M' is at least one of As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb or Ta; and

[0142] A is at least one of F, Cl, Br or I.

[0143] As a solid electrolyte, a material containing sulfur (S), phosphorus (P) and lithium (Li) as constituent elements in a sulfide-based solid electrolyte material can be used. For example, a material containing Li2S-P2S5 can be used. When a material containing Li2S-P2S5 is used as a sulfide-based solid electrolyte material, the mixing molar ratio of Li2S and P2S5 can be selected, for example, in the range of Li2S:P2S5=50:50 to 90:10.

[0144] Furthermore, the solid electrolyte may be in an amorphous or crystalline state. Additionally, the solid electrolyte may be a mixture of amorphous and crystalline forms.

[0145] The solid electrolyte layer 30 may further include a binder (binder). The binder (binder) material may be, for example, a resin such as styrene-butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, or polyacrylic acid. The binder (binder) material may be the same as or different from the material constituting the binder (binder) in the positive electrode active material layer 14 and the negative electrode active material layer 24.

[0146] (4) Composition of all-solid-state lithium-ion secondary batteries

[0147] The all-solid-state lithium-ion secondary battery 100 of the present invention is an all-solid-state lithium-ion secondary battery 100 including a positive electrode 10, a solid electrolyte layer 30 and a negative electrode 20 in sequence. Figure 1The negative electrode 20 includes a negative electrode current collector 22 and a negative electrode active material layer 24, wherein the negative electrode active material layer 24 includes a carbon material and a metal capable of forming an alloy with lithium.

[0148] The negative electrode current collector 22 may include Ni foil, Ni-coated Cu foil, stainless steel foil, or a combination thereof. The negative electrode current collector 22 may have a further improved discharge capacity.

[0149] <Method for manufacturing all-solid-state lithium-ion secondary battery>

[0150] Next, a description will be given of a method for manufacturing the all-solid lithium ion secondary battery 100. The all-solid lithium ion secondary battery 100 according to the embodiment may be obtained by separately manufacturing the cathode 10, the anode 20, and the solid electrolyte layer 30 and then stacking the layers.

[0151] (1) Cathode manufacturing process

[0152] The positive electrode manufacturing process is illustrated as follows. First, the materials constituting the positive electrode active material layer 14 (positive electrode active material, binder (adhesive), etc.) are added to a non-polar solvent to prepare a slurry (or paste). Then, the obtained slurry is applied to the prepared positive electrode collector 12, and it is dried to obtain a laminate. Next, the obtained laminate is pressurized using, for example, hydrostatic pressure to obtain the positive electrode 10. In addition, the pressing process is omitted.

[0153] (2) Negative electrode manufacturing process

[0154] The negative electrode manufacturing process is illustrated as follows. First, the material constituting the negative electrode active material layer 24 (carbon material, metal alloyed with lithium, binder, etc.) is added to a polar solvent or a non-polar solvent to prepare a slurry (which may be a paste). Then, the obtained slurry is applied to the prepared negative electrode current collector 22 to form a negative electrode active material layer.

[0155] If the negative electrode active material layer further includes more than one layer, the additional layers may be stacked in the same manner as described above.

[0156] Next, the laminate obtained by the above method is pressurized using, for example, hydrostatic pressure to manufacture the negative electrode 20. In addition, the pressurization process can be omitted. In addition, the method of applying the slurry to the negative electrode collector 22 is not particularly limited, and for example, it can be a screen printing method, a metal mask printing method, an electrostatic coating method, a dip coating method, a spray coating method, a roll coating method, a doctor blade method, and a gravure coating method.

[0157] Hereinbefore, a method of forming the negative electrode active material layer as two layers has been described, but even in the case of forming an additional layer, slurry for forming each layer is prepared and each layer is sequentially stacked according to the stacking order by the above method to manufacture a negative electrode.

[0158] (3) Solid electrolyte layer manufacturing process

[0159] The solid electrolyte layer 30 may be made of, for example, a solid electrolyte including a sulfide-based solid electrolyte material.

[0160] First, the starting material (such as Li2S, P2S5, etc.) is processed by a melt quenching method or a mechanical grinding method to obtain a sulfide-based solid electrolyte material. For example, when using a melt quenching method, the starting material is mixed in a predetermined amount, and the obtained mixture is granulated, reacted at a predetermined reaction temperature in a vacuum, and then quenched to prepare a sulfide-based solid electrolyte material. In addition, the reaction temperature of the mixture of Li2S and P2S5 can be 400°C to 1000°C, such as 800°C to 900°C. In addition, the reaction time can be 0.1 hours to 12 hours, such as 1 hour to 12 hours. In addition, the quenching temperature of the reactant can be below 10°C, such as below 0°C, and the quenching rate can generally be 1°C / second to 10000°C / second, such as 1°C / second to 1000°C / second.

[0161] In addition, when the mechanical grinding method is used, the starting material is stirred and reacted to prepare the sulfide-based solid electrolyte material using a ball mill, etc. In addition, the stirring speed and stirring time in the mechanical grinding method are not particularly limited, but the faster the stirring speed, the faster the production rate of the sulfide-based solid electrolyte material, and the longer the stirring time, the higher the conversion rate of the raw material to the sulfide-based solid electrolyte material.

[0162] Then, the obtained mixed raw material (sulfide-based solid electrolyte material) is heat-treated at a predetermined temperature and then pulverized to prepare a particulate solid electrolyte. If the solid electrolyte has a glass transition point, it is sometimes transformed from amorphous to crystalline by heat treatment.

[0163] Next, the solid electrolyte obtained by the above method can be formed into a film using, for example, a known film forming method (such as an aerosol positioning method, a cold spray method, or a sputtering method) to prepare a solid electrolyte layer 30. In addition, the solid electrolyte layer 30 can be manufactured by pressing solid electrolyte particles. In addition, the solid electrolyte layer 30 can be prepared by mixing a solid electrolyte, a solvent, and a binder, applying the mixture, and drying and pressing it.

[0164] (4) Stacking process

[0165] The solid electrolyte layer 30 is provided between the cathode 10 and the anode 20 , and they are pressurized using, for example, hydrostatic pressure to obtain the all-solid lithium ion secondary battery 100 according to the embodiment.

[0166] The all-solid lithium ion secondary battery 100 of the present invention can provide improved discharge capacity without applying high external pressure using end plates or the like, and even when the external pressure applied to the positive electrode 10, the negative electrode 20 and the solid electrolyte layer 30 during use is 1 MPa or less.

[0167] <Method for Charging All-Solid-State Lithium-Ion Secondary Battery>

[0168] Next, a charging method of the all-solid lithium ion secondary battery 100 will be described.

[0169] In the charging method of the all-solid lithium ion secondary battery 100 according to the embodiment, the all-solid lithium ion secondary battery 100 may be charged to exceed the charge capacity of the negative electrode active material layer 24 (ie, overcharge).

[0170] When charging starts, lithium can be inserted into the negative electrode active material layer 24. When the battery is charged to exceed the charge capacity of the negative electrode active material layer 24, lithium is precipitated on the back side of the negative electrode active material layer 24, that is, between the negative electrode current collector 22 and the negative electrode active material layer 24, as shown in FIG. Figure 2 As shown, a metal layer 26 that does not exist during manufacturing can be formed by the precipitated lithium. During discharge, the lithium in the negative electrode active material layer 24 and the metal layer 26 is ionized and can migrate toward the positive electrode 10. Therefore, in the all-solid-state lithium ion secondary battery 100 of the present invention, lithium can be used as a negative electrode active material. In addition, since the negative electrode active material layer 24 covers the metal layer 26, it can act as a protective layer for the metal layer 26, and at the same time, the precipitation and growth of dendrite metal lithium can be suppressed. In this way, the short circuit and capacity decline of the all-solid-state lithium ion secondary battery 100 can be suppressed, and in addition, the characteristics of the all-solid-state lithium ion secondary battery 100 can be improved. In addition, according to one embodiment, since the metal layer 26 is not formed in advance, the manufacturing cost of the all-solid-state lithium ion secondary battery 100 can be reduced.

[0171] In addition, the metal layer 26 is not limited to being formed between the negative electrode current collector 22 and the negative electrode active material layer 24. Figure 2 As shown, and may also be formed inside the negative electrode active material layer 24. In addition, the metal layer 26 may be formed between the negative electrode collector 22 and the negative electrode active material layer 24 and inside the negative electrode active material layer 24.

[0172] The all-solid-state lithium-ion secondary battery 100 of the present invention can be manufactured in a unit cell having a structure of positive electrode / separator / negative electrode, a bi-cell having a structure of positive electrode / separator / negative electrode / separator / positive electrode, or a stacked battery structure in which the structure of the unit cell is repeated.

[0173] The shape of the all-solid-state lithium ion secondary battery 100 of the present invention is not particularly limited, and can be exemplified as coin-type, button-type, sheet-like, stacked, cylindrical, flat, horn-type, etc. In addition, it can also be used for large batteries used in electric vehicles, etc. For example, the all-solid-state lithium ion secondary battery 100 can also be used in hybrid vehicles, such as plug-in hybrid electric vehicles (PHEV). In addition, it can be used in fields that require a large amount of power storage. For example, it can be used in electric bicycles or electric tools.

[0174] Hereinafter, in order to specifically describe the present invention, the present invention will be described in detail with reference to embodiments. However, the embodiments of the present invention may be modified in various other forms, and the scope of the present invention should not be construed as being limited to the embodiments described below. Embodiments of the present invention are provided in order to more completely explain the present invention to those of ordinary skill in the art.

[0175] Preparation Example 1: Selecting a carbon material sample with oxygen functional groups introduced

[0176] Various types of commercially available carbon materials were purchased and the oxygen content contained in each carbon material was analyzed in the following manner: Carbon black having an oxygen content of 5.2 atomic % (sample 1), carbon black having an oxygen content of 2.6 atomic % (sample 2), and carbon black having an oxygen content of 1.3 atomic % (sample 3) were selected and used respectively.

[0177] <Analysis Method>

[0178] (1) Analytical instruments

[0179] A photoelectron spectroscopy (XPS or ESCA), K-Alpha (Thermo Fisher Scientific) was used.

[0180] (2) Analysis methods

[0181] First, a full-spectrum scan spectrum and a narrow-scan spectrum were obtained for each sample. The narrow-scan spectrum measured 4 points at each position to obtain the average value and deviation.

[0182] (3) General experimental conditions of ESCA

[0183] X-ray source: monochromatic Al Ka ​​(1486.6 eV)

[0184] X-ray spot size: 400μm

[0185] Operation mode: CAE (Constant Analyzer Energy) mode

[0186] Full spectrum scan: pass energy 200eV, energy step 1eV

[0187] Narrow scan: Scan mode, pass energy 50eV, energy step 0.1eV

[0188] Charge compensation: flood gun off

[0189] SF: Al THERMO1, ECF: TPP-2M, BG minus: Smart

[0190] Table 1:

[0191]

[0192] Example 1 and Comparative Examples 1 to 2: Preparation of slurry of negative electrode active material

[0193] 6 g of carbon black (sample 1, sample 2 or sample 3) with a particle size (D50) of 40 nm to 60 nm, 2 g of Ag with a particle size (D50) of 40 nm to 60 nm, 9.33 g of PVdF binder (6% solid) and 7.19 g of NMP solution were placed in a Thinky mixer container and mixed at 2000 rpm for 12 times for 3 minutes each. Then, 5 g of NMP solution was added and mixed at 2000 rpm for 5 times for 3 minutes each to prepare slurries of the negative electrode active material of Example 1 (using carbon black with an oxygen content of 5.2 atomic %), slurries of the negative electrode active material of Comparative Example 1 (using carbon black with an oxygen content of 2.6 atomic %) and slurries of the negative electrode active material of Comparative Example 2 (using carbon black with an oxygen content of 1.3 atomic %).

[0194] Experimental Example 1: Measurement of particle size of carbon material-metal composite

[0195] (1) Separation of carbon material-metal composite samples

[0196] A portion of the carbon material-metal composite contained in the slurry of the negative electrode active material of Example 1 and Comparative Example 1 was diluted in an NMP solution to prepare an analysis sample.

[0197] (2) Analytical instruments

[0198] The particle size analysis was performed using a Mastersizer 3000 (Malvern panalytical) particle size analyzer.

[0199] Specifically, the carbon material-metal composite analysis sample 1 (Example 1, containing carbon black with an oxygen content of 5.2 atomic %) and the carbon material-metal composite analysis sample 2 (containing carbon black with an oxygen content of 2.6 atomic %) prepared in the above (1) were respectively placed in the sample inlet of the device to achieve laser shielding of 10 to 15%, and measurements were performed.

[0200] The analyzer can analyze particle sizes ranging from 0.01μm to 3500μm and is a particle size analyzer that uses laser diffraction and is suitable for both wet and dry dispersion types.

[0201] (3) Analysis results

[0202] The particle size analysis results of carbon material-metal composite sample 1 and sample 2 are shown in Tables 2 and Figure 3 middle.

[0203] Table 2:

[0204]

[0205] From the results in Table 2, it can be seen that the particle size of the carbon material-metal composite including carbon black having an oxygen content of 5.2 atomic % is significantly smaller than that of the carbon material-metal composite including carbon black having an oxygen content of 2.6 atomic %.

[0206] In addition, according to Figure 3 From the analysis results shown, it can be seen that the maximum particle size of the carbon material-metal composite containing carbon black with an oxygen content of 5.2 atomic % is less than 1 μm, which is significantly smaller than the particle size of the carbon material-metal composite containing carbon black with an oxygen content of 2.6 atomic %.

[0207] Experimental Example 2: Measuring the rheological properties of negative electrode active material slurry

[0208] The rheological properties of the negative electrode active material slurry of Example 1 (using carbon black with an oxygen content of 5.2 atomic %) and the negative electrode active material slurry of Comparative Example 1 (using carbon black with an oxygen content of 2.6 atomic %) were measured using a rheometer model DHR-1 (TAinstrument).

[0209] At this time, a 40 mm parallel plate was used as the geometry, and the viscosity of the slurry according to shear was measured by a flow test. An oscillation frequency test was performed before and after measuring the viscosity.

[0210] The rheological properties are shown in Figure 4 middle.

[0211] In the case of slurries with excellent dispersibility, the rate of viscosity reduction with increasing shear is similar, and the change in viscosity with decreasing shear after increasing shear is also similar. In flow tests, viscosity curvature occurs because the particles are not dispersed, so that large particles interfere with the flow of other small particles.

[0212] like Figure 4 As confirmed in , it was found that the slurry of Example 1 did not show any internal inflection point, and the viscosity changes when the shear rate was increased and then decreased were also almost similar. Therefore, it can be seen from these results that the slurry of Example 1 has excellent dispersibility.

[0213] On the other hand, the slurry of Comparative Example 1 showed an internal inflection point and exhibited irreversible behavior when the shear rate was increased and then decreased. This result means that agglomeration occurred in the slurry.

[0214] Usually, when in 2.5s -1 When the viscosity at a shear rate of 10 Pa·s or less, the slurry has excellent coatability. Under these standards, it was confirmed that the slurry of Example 1 had excellent coatability at 2.5 s -1 The viscosity of the slurry of Comparative Example 1 at a shear rate of 2.5 s was 4.134 Pa·s, and thus it had excellent coatability. -1 The viscosity at a shear rate of is 52.546 Pa·s, so it has poor paintability.

[0215] Example 2 and Comparative Examples 3 to 5: Preparation of Negative Electrode

[0216] The slurry of each negative electrode active material prepared in Example 1 and Comparative Examples 1 and 2 was coated on SUS foil to a thickness of 10 μm and dried to produce the negative electrodes of Example 2 (using carbon black with an oxygen content of 5.2 atomic %), Comparative Example 3 (using carbon black with an oxygen content of 2.6 atomic %), Comparative Example 4 (using carbon black with an oxygen content of 1.3 atomic %) and Comparative Example 5 (using carbon black with an oxygen content of 2.4 atomic %).

[0217] Experimental Example 3: Measurement of oxygen content in the negative electrode active material layer

[0218] The oxygen content contained in the negative electrode active material layer stacked on the negative electrodes prepared in Example 2, Comparative Example 3 and Comparative Example 4 was analyzed in the following manner, and the results are shown in Tables 3, Figure 7 and Figure 8 middle.

[0219] <Analysis Method>

[0220] (1) Analytical instruments

[0221] A photoelectron spectroscopy (XPS or ESCA), Nexsa4 (Thermo Fisher Scientific) was used.

[0222] (2) Analysis methods

[0223] First, a full-spectrum scan spectrum and a narrow-scan spectrum were obtained for each sample. The narrow-scan spectrum measured 4 points at each position and the average and deviation were obtained. Next, a full-spectrum scan spectrum and a narrow-scan spectrum were obtained while performing a depth profile. The depth profile was performed using monatomic Ar ions for up to 5000 seconds.

[0224] (3) Experimental and data processing conditions

[0225] X-ray source: monochromatic Al Ka ​​(1486.6 eV)

[0226] X-ray spot size: 400μm

[0227] Sputtering gun: monatomic Ar (energy: 1000 eV, current: Mid, grating width: 2.0 mm)

[0228] Etching rate: 0.2nm / s Ta2O5 standard (it may vary depending on the sample)

[0229] Operation mode: CAE (Constant Analyzer Energy) mode

[0230] Full spectrum scan: pass energy 200eV, energy step 1eV

[0231] Narrow scan: pass energy 50eV, energy step 0.1eV

[0232] Charge compensation: flood gun off

[0233] SF: Al THERMO1, ECF: TPP-2M, BG minus: Smart

[0234] <Analysis Results>

[0235] (1) Element ratio on the surface of the negative electrode active material layer

[0236] The element ratios of the negative electrode active material layer surface are measured and are shown in Table 3 below.

[0237] Table 3:

[0238]

[0239] It can be seen from the results of Table 3 above that the oxygen content contained in the surface of the negative electrode active material layer is proportional to the oxygen content contained in the carbon material contained in the negative electrode active material layers prepared in Example 2, Comparative Example 3 and Comparative Example 4.

[0240] Figure 7 The 1s spectra of carbon (C) contained in the negative electrode active material layers prepared in Example 2, Comparative Example 3 and Comparative Example 4 are shown. Figure 7 It can be seen that in all the negative electrode active material layers prepared in Example 2, Comparative Example 3 and Comparative Example 4, the chemical states of carbon (C) are similar.

[0241] Figure 8The peak deconvolution results of the O1s spectra of oxygen contained in the negative electrode active material layers prepared in Example 2, Comparative Example 3 and Comparative Example 4 are shown. From the above spectra, it can be seen that as the content of oxygen contained in the carbon material constituting the negative electrode active material layer increases (Example 2> Comparative Example 3> Comparative Example 4), the peak of the metal oxide increases. The peak of the metal oxide seems to be due to the combination of Ag and oxygen on the surface of the carbon material, which just means that the more oxygen on the surface of the carbon material, the better the dispersibility of Ag.

[0242] Table 4 below shows numerically Figure 8 .

[0243] Table 4:

[0244]

[0245] Experimental Example 4: Measurement of surface roughness of negative electrode active material layer

[0246] The surface roughness of the negative electrode active material layers stacked on the negative electrodes prepared in Example 2 and Comparative Example 5 was measured using a 3D laser confocal microscope apparatus (manufactured by KEYENCE Corporation).

[0247] Specifically, the negative electrode for measuring roughness was prepared in an appropriate size. At this time, in order to ensure data reliability and check the deviation of roughness within the sample, more than three samples were prepared for the same electrode. These samples were attached to a glass slide using double-sided tape to avoid wrinkling.

[0248] The glass slide with the prepared sample attached is placed on the measuring stage, and then focused and the roughness is measured.

[0249] SEM images of the negative electrode active material layers stacked on the negative electrodes prepared in Example 2 and Comparative Example 5 are shown in FIG. Fig. 9 The surface roughness measurements are shown in Tables 5 and Fig.10 middle.

[0250] Table 5:

[0251] Sa(μm) Sz(μm) <![CDATA[Spc(mm -1 )]]> Sdn Example 2 0.073 1.377 994 0.0198 Comparative Example 5 0.528 9.737 2408 0.2150

[0252] Experimental Example 5: Analysis of Density and Porosity of Negative Electrode Active Material Layer

[0253] The density and porosity of the negative electrode active material layers stacked on the negative electrodes prepared in Example 2 and Comparative Examples 3 to 5 were calculated, and the results are shown in Table 6 below.

[0254] Table 6:

[0255]

[0256] Preparation of All-Solid-State Lithium Ion Secondary Batteries of Example 3 and Comparative Examples 6 and 7

[0257] Used in current collector with 5 mAh / cm 2 A positive electrode loaded with a positive electrode active material is used as the positive electrode, the negative electrode prepared in Example 2 and Comparative Examples 3 to 4 is used as the negative electrode, and a sulfide-based all-solid-state electrolyte (LPSCl composition) is used as the electrolyte to manufacture the pouch-type single cells of Example 3, Comparative Example 6 and Comparative Example 7.

[0258] Experimental Example 6: Evaluation of battery characteristics

[0259] The pouch-type single cells of Example 3, Comparative Example 6 and Comparative Example 7 were operated under the following charge / discharge conditions in an operating voltage range of 4.25 V to 3.0 V and an operating temperature of 60° C. to evaluate the cycle characteristics, and the results are shown in Figure 5 and 6 middle.

[0260] Charging conditions: 0.33C, 4.25V CC / CV, 0.1C cut-off

[0261] Discharge conditions: 0.33C, 3.0V, CC

[0262] from Figure 5 It can be seen that in the case of the battery cell of Example 3, it operates without a significant decrease in the battery cell capacity as the cycle proceeds.

[0263] In addition, from Figure 6 It can be seen that the battery cell of Example 3 has significantly better cycle characteristics than the battery cells of Comparative Examples 6 and 7.

Claims

1. A negative electrode, comprising: current collector; as well as negative electrode active material layer, The negative electrode active material layer includes more than one layer, and any one of the negative electrode active material layers contains oxygen in an amount of 2 atomic % to 10 atomic %.

2. The negative electrode according to claim 1, wherein Either negative electrode active material layer further contains 65 atomic % to 85 atomic % of carbon and 0.5 atomic % to 5 atomic % of a metal element.

3. The negative electrode according to claim 2, wherein Either negative electrode active material layer contains carbon material particles and metal particles.

4. The negative electrode according to claim 3, wherein The carbon material particles are amorphous carbon material particles.

5. The negative electrode according to claim 3, wherein The carbon material particles contain 3 atomic % to 10 atomic % of oxygen.

6. The negative electrode according to claim 5, wherein The oxygen exists in the form of being contained in a functional group bonded to the carbon material particles.

7. The negative electrode according to claim 6, wherein The functional group includes at least one selected from the group consisting of a carboxyl group, a hydroxyl group, an ether group, an ester group, an aldehyde group, a carbonyl group, and an amide group.

8. The negative electrode according to claim 3, wherein The metal particles are particles that form an alloy with lithium.

9. The negative electrode according to claim 8, wherein The metal particles are one or more particles selected from the group consisting of silver (Ag), gold, platinum, palladium, silicon, aluminum, bismuth, tin, indium and zinc.

10. The negative electrode according to claim 9, wherein The metal particles include silver (Ag).

11. The negative electrode according to claim 1, wherein Any negative electrode active material layer has the following surface roughness: 0.01μm≤Sa≤0.3μm 0.5μm≤Sz≤5μm 500mm -1 ≤Spc≤1500mm -1 0.005≤Sdr≤0.

15.

12. The negative electrode according to claim 1, wherein The porosity of any negative electrode active material layer was 55% to 70%.

13. The negative electrode according to claim 3, wherein The carbon material particles and the metal particles are included in the form of a carbon material-metal composite.

14. The negative electrode according to claim 13, wherein The particle size D50 of the carbon material-metal composite is 0.1 μm to 0.5 μm.

15. The negative electrode according to claim 14, wherein The maximum particle size of the carbon material-metal composite is 3 μm or less.

16. A lithium ion secondary battery comprising: The negative electrode according to claim 1; positive electrode; as well as An electrolyte is interposed between the negative electrode and the positive electrode.

17. The lithium ion secondary battery according to claim 16, wherein: The electrolyte includes a sulfide-based solid electrolyte.

18. The lithium ion secondary battery according to claim 17, wherein: The lithium ion secondary battery is an anode-free battery.

Citation Information

Patent Citations

  • Positive electrode for rechargeable lithium battery and rechargeable lithium battery including the same

    KR1020150064697A

  • Method for producing a stator arrangement

    KR1020220144769A

  • Display panel, and electronic apparatus including the same

    KR1020230148135A